Livelihood activities and well-being outcomes of cash transfer beneficiaries in Soweto, South Africa. Issue 1 (2nd January 2022) - Nnaeme, Chibuikem C.; Patel, Leila; Plagerson, Sophie
ABSTRACT: Despite a growing body of research on the benefits of cash transfers in reducing poverty, limited knowledge exists of beneficiaries' usage of social assistance to pursue livelihood activities in urban areas. This qualitative narrative enquiry provides empirical evidence that when cash transfers are combined with a wide range of livelihood activities, then material and psychosocial as well as personal, household, and business outcomes are improved. Evidence from Soweto, South Africa, provides policy and programmatic solutions for low- and middle-income countries which can inform post-covid responses to mitigate health and livelihood shocks and the deepening of poverty levels.